Impact of the SARS-CoV-2 infection in individuals with sickle cell disease: an integrative review - Pereira, Laura Resende Guimarães; da Silva, Maria Vitoria Gomes; Germano, Carla Maria Ramos; Estevao, Isabeth F.; Melo, Débora Gusmão (Frontiers in Medicine, 2023)
Sickle cell disease is the most common hemoglobinopathy among humans. As the condition promotes susceptibility to infections, chronic inflammation, and hypercoagulability disorders, several international agencies have included individuals with this disease in the COVID-19 risk group for severe outcomes. However, available information about the subject is not properly systematized yet. This review aimed to understand and summarize the scientific knowledge about the impact of SARS-CoV-2 infection in patients with sickle cell disease. Searches were performed in the Medline, PubMed, and Virtual Health Library databases based on descriptors chosen according to the Medical Subject Headings. We analyzed studies published between 2020 and October 2022, developed with qualitative, quantitative, or mixed methodology, and written in English, Spanish, or Portuguese. The search resulted in 90 articles organized into six categories. There is disagreement in the literature about how different aspects related to sickle cell disease, such as chronic inflammation status, hypercoagulability, hemolytic anemia, use of hydroxyurea, and access to medical care interference with the clinical course of COVID-19. These topics deserve further investigation. It is evident, however, that the infection may manifest in an atypical way and act as a trigger for the development of sickle cell-specific complications, such as acute chest syndrome and vaso-occlusive crises, conditions that are associated with great morbidity and mortality. Therefore, healthcare professionals must be aware of the different forms of presentation of COVID-19 among these individuals. Specific guidelines and therapeutic protocols, as well as public policies for sickle cell individuals, must be considered.